C allele of ‐786 T>C polymorphism in the promoter region of endothelial nitric oxide synthase is responsible for endothelial dysfunction in the patients with rheumatoid arthritis. Issue 1 (18th June 2019) - Luo, Yanli; Wang, Yang; Luo, Wanjun
Abstract: Background: This study aimed to explore the roles of endothelial nitric oxide synthase (eNOS) in the control of metastasis of infection with endothelial dysfunction, as well as the roles of ‐786T>C polymorphism in eNOS promoter in the control of metastasis of endothelial function. Method: In‐silicon analysis and luciferase assay were used to identify the location of ‐786>C on the promoter of eNOS. Subsequently, real‐time PCR and Western‐blot were used to determine the expression level of eNOS. Ultrasound examination was used to detect baseline brachial artery diameter and flow‐mediated dilation of patients in different treat groups. Results: ‐786T>C was located on the promoter of eNOS, and the luciferase activity of cells transfected with ‐786‐C allele was much higher than empty vector, while even higher subsequent to transfection of ‐786‐T allele. In addition, the result of ultrasound examination showed that the baseline brachial artery diameter was comparable between patients genotyped as TT, TC and CC, while the flow‐mediated dilation of patients genotyped as TC was much higher compared with CC group, and the flow‐mediated dilation of patients genotyped as TT even higher than TC group. We found eNOS messenger RNA and protein with TT genotype was significantly higher compared with other genotypes. And the production of NO was remarkably higher in TT groups compared with TC and CC, while the production of NO in TC and CC groups were similar. Conclusion: These findings indicated that down‐expression of ‐786T>C located on the promoter of eNOS is associated with an increased risk of endothelial dysfunction. Abstract : This study aimed to explore the roles of endothelial nitric oxide synthase (eNOS) in the control of metastasis of infection with endothelial dysfunction, and how ‐786T>C polymorphism in gene promoter in the control of metastasis of endothelial function. Accordingly, these findings provide support that down‐expression of ‐786T>C located on the promoter of eNOS is associated with an increased risk of endothelial dysfunction.